Amygdala–Cortical Connectivity: Associations with Anxiety, Development, and Threat. Issue 10 (October 2016) - Gold, Andrea L.; Shechner, Tomer; Farber, Madeline J.; Spiro, Carolyn N.; Leibenluft, Ellen; Pine, Daniel S.; Britton, Jennifer C.
Abstract : Background: Amygdala–prefrontal cortex (PFC) functional connectivity may be influenced by anxiety and development. A prior study on anxiety found age‐specific dysfunction in the ventromedial PFC (vmPFC), but not amygdala, associated with threat‐safety discrimination during extinction recall (Britton et al.8 ). However, translational research suggests that amygdala–PFC circuitry mediates responses following learned extinction. Anxiety‐related perturbations may emerge in functional connectivity within this circuit during extinction recall tasks. The current report uses data from the prior study to examine how anxiety and development relate to task‐dependent amygdala–PFC connectivity. Methods: Eighty‐two subjects (14 anxious youths, 15 anxious adults, 25 healthy youths, 28 healthy adults) completed an extinction recall task, which directed attention to different aspects of stimuli. Generalized psychophysiological interaction analysis tested whether task‐dependent functional connectivity with anatomically defined amygdala seed regions differed across anxiety and age groups. Results: Whole‐brain analyses showed significant interactions of anxiety, age, and attention task (i.e., threat appraisal, explicit threat memory, physical discrimination) on left amygdala functional connectivity with the vmPFC and ventral anterior cingulate cortex (Talairach XYZ coordinates: −16, 31, −6 and 1, 36, −4). During threat appraisal and explicit threat memory (vs. physical discrimination), anxious youth showed more negative amygdala–PFC coupling, whereas anxious adults showed more positive coupling. Conclusions: In the context of extinction recall, anxious youths and adults manifested opposite directions of amygdala–vmPFC coupling, specifically when appraising and explicitly remembering previously learned threat. Future research on anxiety should consider associations of both development and attention to threat with functional connectivity perturbations.